Prevalence and Risk Factors of Cardiotoxicity in Patients with Multidrug Resistant Tuberculosis Infection Receiving a Shorter All-oral Bedaquiline-containing Regimen - Cheilweit, Chantawat; Deewech, Piyawan; Limtrakul, Punnut; Boonruang, Rattanaporn; Sangsayan, Piamlap; Tewthanom, Karunrat (Asian Health, Science and Technology Reports, 2023)
The most important adverse effect of bedaquiline is QT prolongation. There have not been any definitive studies on the prevalence of QT prolongation caused by bedaquiline drugs used in Thailand. Therefore, the purpose of this retrospective chart review study was to estimate the prevalence and risk factors of QT prolongation in patients with multidrug-resistant tuberculosis (MDR-TB) infection who were receiving a shorter all-oral bedaquiline-containing regimen. The data of the MDR-TB patients who received this treatment regimen between June 1, 2020, and December 31, 2021, at the Central Chest Institute of Thailand and Makaruk Hospital were collected. The event of QTc prolongation and risk factors, including QTc baseline, gender, QT prolongation diagnosed by physician, potassium level, comorbidities, and other drugs used in the shorter all-oral Bedaquiline-containing regimen, were recorded. Results showed that, from 33 patients (19 men and 14 women, age 43.24±15.79 years) with multidrug-resistant tuberculosis infection who received treated under this regimen, 27 (81.82%) of the patients received levofloxacin-based regimen, and 2 of the patients (6.06%) had QT prolongation. Other factors that may contribute to the development of QT prolongation are hypokalemia and other drugs used in this regimen. This study may lead to the development of a risk assessment tool for monitoring QT prolongation in patients who receive the shorter all-oral bedaquiline-containing regimen.